IDENTIFIKASI AWAL POTENSI EKSTRAK ETANOL RIMPANG JAHE MERAH (Zingiber officinale Rosc. var. rubrum) SEBAGAI OBAT OSTEOPOROSIS - Aqnes Budiarti; Devi Nisa Hidayati; Nur Aini (Universitas Wahid Hasyim Semarang, 2017)
ABSTRACT Reduced bone density is an indication of osteoporosis. The study of osteoporosis is conducted by measure the influence of triggering compound to the enhancement of bone density of ovariectomized rat that have been lifted ovaries. Ovariectomy caused rats have been deficiency of estrogen hormone whose function to maintain bone density.Compound that can increase bone density has the potential as osteoporosis drug. Red ginger rhizome contains flavonoid compound as phytoestrogen whose estrogenic effect that can replace the function of estrogen. Flavonoid is easy to be solved in ethanol so that was extracted using ethanol. The purpose of this study was to measure the enhancement of bone density of ovariectomized rats due to the trigger of ethanol extract of red ginger (EERJM). Research was conducted experimentally to the female Wistar rats by the post test only controlled group design. Treatment was given for 30 days and the determination of bone density using Dual X-Ray radiography method. Data of bone density values were statistically analyzed by One Way ANOVA followed by Tukey test. The results showed that the administration of EERJM dose 500 and 1000 mg/kg BW enhanced bone density of ovariectomized rat. Keywords: bone density, ovariectomized rat, red ginger, osteoporosis